ELIPSIS PADA WACANA TENTANG COVID-19 DALAM KOLOM OPINI SURAT KABAR KOMPAS - Bonefasius Rampung; Antonius Nesi; Petrus Sii (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
This study aims to describe the ellipsis construction or removal of language elements in the discourse about corana virus diseases (Covid-19) in the Kompas newspaper opinion column. The discourses analyzed were sourced from Kompas opinions published from March to April 2020. The method used in data collection was the refer to method (read), which was applied through the note taking technique. The stages of data collection in this study, namely the inventory, identification and classification of data. The method of data analysis in this study is the agih method, which is applied with the technique of fade and replace for direct elements. Stages of data analysis in this study, namely reduction, interpretation, presentation, and discussion of the results of data analysis. The results of this research data analysis show that the ellipsis construction in the discourse about Covid-19 in the Kompas newspaper opinion column consists of the subject ellipsis, the subject ellipsis as well as the predicate, and the object ellipsis in equivalent (coordinative) compound sentences. Meanwhile, the ellipsis compound compound (subordinate) occurs in the function of the subject, both in the child clause (clause) and in the parent clause (parent sentence). Both in equivalent compound sentences and in multilevel compound sentences, the elements in each function are written in words both cataphoric and anaphoric.